Enhancing the Utilization of Research Findings from Departments of Educational Planning and Management in Nigerian Tertiary Institutions for Evidence-Based Policy and Educational Development - Peace Ogechukwu IGWE (Researchparks Publishing, 2026)
Research remains one of the most important functions of tertiary institutions because it provides evidence for solving educational problems and improving policy decisions. Departments of Educational Planning and Management in Nigerian universities, colleges of education, and other higher institutions generate numerous research findings on educational finance, school administration, policy implementation, quality assurance, teacher management, leadership, and institutional development. Despite the growing volume of research outputs, many of these findings are not adequately utilized by public and private organizations responsible for educational planning and administration. This situation has created a persistent gap between educational research and policy implementation. This paper reviews factors that can enhance the effective utilization of research findings generated from Departments of Educational Planning and Management in Nigerian tertiary institutions. The review identifies university-policy maker collaboration, effective dissemination mechanisms, knowledge transfer structures, accessibility of research outputs, policy-relevant research agendas, capacity building for educational administrators, adequate funding, and evidence-based decision-making culture as critical factors for improving research utilization. The paper argues that educational development can be accelerated when research findings are systematically integrated into policy formulation, planning processes, programme implementation, and institutional management. The study concludes that strengthening the linkage between researchers and educational stakeholders will improve the contribution of tertiary institutions to educational transformation and national development.